Intervention effects of traditional Chinese medicine on stem cell therapy of myocardial infarction - Wang, Yu; Xue, Yuezhen; Guo, Hai-dong (Frontiers in Pharmacology, 2022)
Cardiovascular diseases are the leading cause of global mortality, in which myocardial infarction accounts for 46% of total deaths. Although good progress has been achieved in medication and interventional techniques, a proven method to repair the damaged myocardium has not yet been determined. Stem cell therapy for damaged myocardial repair has evolved into a promising treatment for ischemic heart disease. However, low retention and poor survival of the injected stem cells are the major obstacles to achieving the intended therapeutic effects. Chinese botanical and other natural drug substances are a rich source of effective treatment for various diseases. As such, numerous studies have revealed the role of Chinese medicine in stem cell therapy for myocardial infarction treatment, including promoting proliferation, survival, migration, angiogenesis, and differentiation of stem cells. Here, we discuss the potential and limitations of stem cell therapy, as well as the regulatory mechanism of Chinese medicines underlying stem cell therapy. We focus on the evidence from pre-clinical trials and clinical practices, and based on traditional Chinese medicine theories, we further summarize the mechanisms of Chinese medicine treatment in stem cell therapy by the commonly used prescriptions. Despite the pre-clinical evidence showing that traditional Chinese medicine is helpful in stem cell therapy, there are still some limitations of traditional Chinese medicine therapy. We also systematically assess the detailed experimental design and reliability of included pharmacological research in our review. Strictly controlled animal models with multi-perspective pharmacokinetic profiles and high-grade clinical evidence with multi-disciplinary efforts are highly demanded in the future.